Prevalence of depression in tuberculosis patients in comparison with non-tuberculosis family contacts visiting the DOTS clinic in a Nigerian tertiary care hospital and its correlation with disease pattern - Ige, Olusoji Mayow (Radcliffe Publishing Ltd., 2011)
Background Individuals with chronic diseases such as tuberculosis often have comorbid de-pression that requires frequent hospitalisations. This poses great challenges to the care of such patients. Objective This study aimed at determining the prevalence of depression in tuberculosis patients in comparison with non-tuberculosis controls, and its correlation with disease pattern. Method Eighty-eight patients with tuberculosis and 81 family members visiting the DOTS Centre at University College Hospital Ibadan Centre were screened for depression. Severity of depression was assessed using the Hamilton Depression Scale and was compared with severity of pulmonary tuberculosis. Results The prevalence of depression was 45.5% among patients and 13.4% among family members. Depression was more prevalent among patients that were elderly (P = 0.001), with extensive disease (P = 0.01), of long duration (P = 0.03), those with category 2 tuberculosis (P = 0.003), those from a nuclear family (P = 0.01) and patients that were unmarried (P = 0.02). Conclusion The impact of chronic diseases such as tuberculosis extends beyond physical impairment. It includes behavioural consequences, in this instance depression, for both the patient and the primary care givers. Thus, the care of patients with tuberculosis should be comprehensive and include consultative–liaison psychiatric care.